A silicon dioxide ceramic and its preparation method and application

By modifying silica and combining other fluxes and fibers, ceramic fillers with good compatibility with silicone rubber were developed, which solved the problem of insufficient performance of existing fire-resistant cables under fire conditions, and achieved high performance and high fire resistance of ceramicized silicone rubber.

CN119144050BActive Publication Date: 2025-04-25LINYI JINGSHI CERAMICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411273486.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-04-25
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

Existing fire-resistant cables are expensive under fire conditions, complex production processes, prone to moisture short circuits, high cost and not fully fire-proofing effects, and cannot fully meet practical requirements.

Method used

Develop a silica-based ceramic filler with good compatibility with silicone rubber. By initial doping and coating modification and hydrophobic modification of silica, it combines fluxes such as low-melting point glass powder, boron oxide, zinc borate, and materials such as silicon micropowder, high-temperature flame retardant fibers to form ceramic silicone rubber composite materials.

Benefits of technology

The mechanical properties, flame retardant properties, thermal stability and ceramicization properties of ceramicized silicone rubber are significantly improved, making it suitable for high-fire-proof applications such as fire-resistant cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144050B_ABST
    Figure CN119144050B_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon dioxide ceramic and its preparation method and application, belonging to the technical field of refractory ceramic materials. The silicon dioxide ceramic of the present invention comprises the following raw materials in parts by weight: 40-60 parts of ceramic filler, 30-60 parts of silicon dioxide reinforcing material, 3-5 parts of flux, 5-10 parts of incremental filler, and 10-15 parts of high temperature resistant flame retardant fiber. The present invention develops a new filler composition for ceramic silicone rubber, which effectively improves its compatibility with the matrix through the effective modification of silicon dioxide, and the obtained ceramic silicone rubber has good fire resistance, and the flame retardant property and mechanical property are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory ceramic materials, and specifically relates to a silicon dioxide ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, fires have occurred frequently in chemical, coal mines, and large entertainment venues, causing great losses to people's lives and property, and making people have a deeper understanding of fire protection and fire safety. How to ensure smooth power and communication within a certain period of time in the event of a fire, maximize precious time, and reduce casualties and property losses is a problem that people need to seriously consider and continuously explore. Fire-resistant cables can ensure the normal operation of the line when a fire occurs, which is of great help to rescue work and can greatly reduce casualties and property losses.

[0003] The so-called fire-resistant cable is a cable that can maintain normal operation for a certain period of time under specified flame combustion conditions; or a cable that can maintain the integrity of the line for a certain period of time under combustion conditions. At present, the most commonly used at home and abroad are mineral insulated fire-resistant cables and mica tape wrapped fire-resistant cables. However, due to the special composition and structure of mineral insulated fire-resistant cables, the price is expensive, the production process and installation construction process are complicated, and the minerals are easily affected by moisture and short-circuited, which greatly limits the use of this cable. The manufacturing process of mica tape wrapped fire-resistant cables is complicated and the cost is high. After the fire, the cable insulation layer may be transformed into a carbonized layer, which conducts electricity when it comes into contact with water and does not play a real fire-resistant role. Due to the many limitations mentioned above, these two types of fire-resistant cables cannot fully meet practical requirements.

[0004] Ceramic composite silicone rubber plays an important role in solving the problem of cables being unusable due to short circuits in fires. Unlike ordinary silicone rubber, this material exhibits the properties of ordinary silicone rubber at room temperature, but can be transformed into a hard ceramic-like substance when exposed to high temperatures in fire, forming an insulating protective layer, thereby ensuring the smooth flow of electricity and communications during fires.

[0005] However, ceramic silicone rubber needs to be filled with a large amount of ceramic fillers to achieve a stable flame retardant effect. Untreated fillers tend to agglomerate and have poor dispersion in silicone rubber, which will greatly reduce the mechanical properties of the prepared ceramic silicone rubber, and the flame retardant and heat resistance will also be affected. On the other hand, the melting point of the main fillers used in the ceramic silicone rubber formula is very high. To truly ceramicize, the sintering temperature must reach 1000℃ or even above 1500℃.

[0006] In view of the above reasons, it is a technical problem that needs to be solved urgently to develop a filler that has good compatibility with silicone rubber and is highly flame retardant while maintaining the high strength and original shape of the ceramic product. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a silica-based ceramic filler which has good compatibility with silicone rubber and is evenly dispersed, and can greatly improve the mechanical properties, flame retardant properties, thermal stability and ceramic properties of the rubber.

[0008] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0009] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 40-60 parts of a ceramic filler, 30-60 parts of a silicon dioxide reinforcing material, 3-5 parts of a flux, 5-10 parts of an incremental filler, and 10-15 parts of high temperature resistant flame retardant fibers.

[0010] Furthermore, the ceramic-forming filler is one or more of mica powder, aluminum hydroxide, clay, calcium carbonate, and kaolin.

[0011] Furthermore, the flux is one or more of low-melting-point glass powder, boron oxide, and zinc borate. The melting point of the low-melting-point glass powder is 400-500°C.

[0012] Furthermore, the silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0013] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20-30 minutes, heating in a tube furnace at 400-500° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0014] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0015] Furthermore, the particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0016] Furthermore, the modifier solution is obtained by dispersing a long-chain silane in an ethanol solution, and the long-chain silane is one of n-dodecyltrimethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane or octadecyltriethoxysilane.

[0017] Furthermore, the incremental filler is silicon powder.

[0018] Furthermore, the high temperature resistant flame retardant fiber is basalt fiber, glass fiber or aluminum silicate fiber.

[0019] A method for preparing silicon dioxide ceramics comprises the following steps:

[0020] (1) preparing a silicon dioxide reinforcing material;

[0021] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0022] (3) Add deionized water in an amount of 8 to 10 times the mass of the mixed base material to the dry premix, put it into a ball mill, control the ball-to-material ratio to 1:1, wet ball mill at 300 to 500 r / min for 1 to 3 hours, filter, dry, and crush to obtain a ball mill material, and after drying, obtain the final product.

[0023] The silicon dioxide ceramic of the present invention is added to silicone rubber and used as a ceramic filler when it is actually used. The prepared ceramic silicone rubber has heat-resistant and flame-retardant properties and can be used as a fireproof cable in particular.

[0024] All raw materials of the present invention are commercially available.

[0025] Silicone rubber has the advantages of high and low temperature resistance, electrical insulation, UV resistance and chemical corrosion resistance, and has been widely used. However, due to its poor fire resistance, its application is subject to certain restrictions. The development of ceramic silicone rubber composite materials is one of the solutions to the high fire protection application needs. At present, ceramic fillers are mainly inorganic silicates, including mica, wollastonite, silica and clay.

[0026] Silica is a commonly used filler composition, but it has many problems, such as dispersion problems, resulting in agglomeration, decreased uniformity of the substrate, and thus decreased mechanical properties and thermodynamic properties such as thermal expansion, resulting in decreased heat resistance and flame retardancy of the entire material.

[0027] Based on the above considerations, the present invention first uses sodium saccharin and ammonium polyphosphate to perform preliminary doping and coating modification on silicon dioxide. The treatment of sodium saccharin and ammonium polyphosphate, ammonium polyphosphate contains a high proportion of phosphorus and nitrogen elements, and sodium saccharin contains sulfur and nitrogen elements at the same time, so that the surface of silicon dioxide is doped with N, P, and S elements at the same time, which can significantly improve its fire retardant properties. Sodium saccharin and ammonium polyphosphate work together, and N, P, and S are deposited on the surface of nanoparticles to form a composite flame retardant, thereby enhancing its flame retardant effect. Subsequently, the present invention uses a low concentration to a high concentration of long-chain silane coupling agent to modify the surface of silicon dioxide particles. The long-chain coupling agent can fully react with the silicon hydroxyl group on the surface of silicon dioxide and graft to the surface of silicon dioxide. At the same time, the longer organic chain segment can provide a significant steric hindrance effect, which makes it difficult for the filler particles to interact with each other, thereby avoiding bonding and aggregation between particles. In addition, not only the properties of the filler surface are changed, but also the bonding between the filler and the polymer matrix is ​​enhanced by chemical bonding. This chemical bonding further improves the dispersion and stability of the filler in the organic matrix, ensuring the overall performance of the material.

[0028] In addition, the present invention adds low-melting point glass powder, boron oxide, zinc borate, etc. as flux, which can further reduce the ceramicization temperature and increase the ceramicization speed. The addition of silicon micropowder can adjust the hardness of the vulcanized rubber and improve the process performance during the silicone rubber process. The addition of heat-resistant fibers such as aluminum silicate fibers can effectively block the penetration of oxygen in the air, thereby improving the ablation resistance of the composite material. Heat-resistant fibers such as aluminum silicate fibers can also improve the overall performance of the composite material by enhancing its mechanical properties. This is because heat-resistant fibers such as aluminum silicate fibers can consume part of the energy at high temperatures, thereby hindering the expansion of cracks and reducing the self-weight deformation of the material.

[0029] In summary, the beneficial effects of the technical solution of the present invention are:

[0030] The present invention develops a new filler composition for ceramic silicone rubber, which effectively improves the compatibility of silicon dioxide with a matrix through effective modification of silicon dioxide. The obtained ceramic silicone rubber has good fire resistance, and the flame retardant property and mechanical properties are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The microscopic morphology of the cross section of the silicone rubber ceramic body prepared using Example 1 of the present invention and Comparative Examples 1-5 as fillers. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0033] Example 1

[0034] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 40 parts of ceramic filler, 30 parts of silicon dioxide reinforcing material, 5 parts of flux, 5 parts of incremental filler, and 10 parts of high temperature resistant flame retardant fiber.

[0035] The ceramic-forming filler is mica powder.

[0036] The flux is low melting point glass powder.

[0037] The melting point of the low-melting-point glass powder is 400-500°C.

[0038] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0039] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20 minutes, heating in a tube furnace at 400° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0040] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0041] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0042] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is n-dodecyltrimethoxysilane.

[0043] The incremental filler is silicon powder.

[0044] The high temperature resistant flame retardant fiber is basalt fiber.

[0045] A method for preparing silicon dioxide ceramics comprises the following steps:

[0046] (1) preparing a silicon dioxide reinforcing material;

[0047] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0048] (3) The dry premix is ​​added with deionized water in an amount 8 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 300 r / min for 1 hour, filtered, dried, and crushed to obtain a ball mill material, and dried to obtain the final product.

[0049] Example 2

[0050] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 50 parts of a ceramic filler, 50 parts of a silicon dioxide reinforcing material, 4 parts of a flux, 6 parts of an incremental filler, and 11 parts of high-temperature resistant flame-retardant fibers.

[0051] The porcelain-forming filler is aluminum hydroxide.

[0052] The flux is boron oxide.

[0053] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0054] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 25 minutes, heating in a tube furnace at 450° C. for 2 hours, and naturally cooling to room temperature after heating to obtain preliminarily modified nano-silica;

[0055] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0056] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0057] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is hexadecyltrimethoxysilane.

[0058] The incremental filler is silicon powder.

[0059] The high temperature resistant flame retardant fiber is glass fiber.

[0060] A method for preparing silicon dioxide ceramics comprises the following steps:

[0061] (1) preparing a silicon dioxide reinforcement material;

[0062] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0063] (3) The dry premix is ​​added with deionized water in an amount 8 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 400 r / min for 2 hours, filtered, dried, and crushed to obtain a ball milled material, and dried to obtain the final product.

[0064] Example 3

[0065] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 45 parts of a ceramic filler, 40 parts of a silicon dioxide reinforcing material, 3 parts of a flux, 7 parts of an incremental filler, and 13 parts of high-temperature resistant flame-retardant fibers.

[0066] The porcelain-forming filler is clay.

[0067] The flux is zinc borate.

[0068] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0069] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 30 minutes, heating in a tube furnace at 400° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0070] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0071] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1:1.

[0072] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is hexadecyltriethoxysilane.

[0073] The incremental filler is silicon powder.

[0074] The high temperature resistant flame retardant fiber is aluminum silicate fiber.

[0075] A method for preparing silicon dioxide ceramics comprises the following steps:

[0076] (1) preparing a silicon dioxide reinforcing material;

[0077] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0078] (3) The dry premix is ​​added with deionized water in an amount 10 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 500 r / min for 1 hour, filtered, dried, and crushed to obtain a ball mill material, and dried to obtain the final product.

[0079] Example 4

[0080] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 55 parts of a ceramic filler, 45 parts of a silicon dioxide reinforcing material, 4 parts of a flux, 8 parts of an incremental filler, and 12 parts of high temperature resistant flame retardant fibers.

[0081] The porcelain-forming filler is kaolin.

[0082] The flux is low-melting-point glass powder, and the melting point of the low-melting-point glass powder is 400-500°C.

[0083] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0084] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20 minutes, heating in a tube furnace at 500° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0085] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0086] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0087] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is octadecyltrimethoxysilane.

[0088] The incremental filler is silicon powder.

[0089] The high temperature resistant flame retardant fiber is obtained by mixing glass fiber and aluminum silicate fiber in a mass ratio of 1:1.

[0090] A method for preparing silicon dioxide ceramics comprises the following steps:

[0091] (1) preparing a silicon dioxide reinforcing material;

[0092] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0093] (3) The dry premix is ​​added with deionized water in an amount 8 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 300 r / min for 3 hours, filtered, dried, and crushed to obtain a ball mill material, and dried to obtain the final product.

[0094] Example 5

[0095] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 60 parts of a ceramic filler, 60 parts of a silicon dioxide reinforcing material, 3 parts of a flux, 10 parts of an incremental filler, and 15 parts of high-temperature resistant flame-retardant fibers.

[0096] The porcelain-forming filler is obtained by mixing mica powder, clay and kaolin in a mass ratio of 1:1:1.

[0097] The flux is low-melting-point glass powder, and the melting point of the low-melting-point glass powder is 400-500°C.

[0098] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0099] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 30 minutes, heating in a tube furnace at 500° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0100] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0101] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0102] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is octadecyltriethoxysilane.

[0103] The incremental filler is silicon powder.

[0104] The high temperature resistant flame retardant fiber is aluminum silicate fiber.

[0105] A method for preparing silicon dioxide ceramics comprises the following steps:

[0106] (1) preparing a silicon dioxide reinforcing material;

[0107] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0108] (3) The dry premix is ​​added with deionized water in an amount 10 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 500 r / min for 3 hours, filtered, dried, and crushed to obtain a ball-milled material, and dried to obtain the final product.

[0109] Comparative Example 1

[0110] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 40 parts of ceramic filler, 30 parts of silicon dioxide, 5 parts of flux, 5 parts of incremental filler, and 10 parts of high-temperature resistant flame-retardant fiber.

[0111] The ceramic-forming filler is mica powder.

[0112] The flux is low melting point glass powder.

[0113] The melting point of the low-melting-point glass powder is 400-500°C.

[0114] The particle size of the nano silicon dioxide is 30-50nm;

[0115] The incremental filler is silicon powder.

[0116] The high temperature resistant flame retardant fiber is basalt fiber.

[0117] A method for preparing silicon dioxide ceramics comprises the following steps:

[0118] (1) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0119] (2) The dry premix is ​​added with deionized water in an amount 8 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 300 r / min for 1 hour, filtered, dried, and crushed to obtain a ball mill material, and dried to obtain the final product.

[0120] In this comparative example, except that nano silicon dioxide is directly used, the other raw materials and preparation methods are the same as those in Example 1.

[0121] Comparative Example 2

[0122] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 40 parts of ceramic filler, 30 parts of silicon dioxide reinforcing material, 5 parts of flux, 5 parts of incremental filler, and 10 parts of high temperature resistant flame retardant fiber.

[0123] The ceramic-forming filler is mica powder.

[0124] The flux is low melting point glass powder.

[0125] The melting point of the low-melting-point glass powder is 400-500°C.

[0126] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0127] (1) placing nano-silicon dioxide in a container and grinding it for 20 minutes, heating it in a tube furnace at 400° C. for 2 hours, and then naturally cooling it to room temperature after the heating is completed to obtain preliminarily modified nano-silicon dioxide;

[0128] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% respectively for 1 hour, for a total of 3 hours. After soaking, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0129] The particle size of the nano silicon dioxide is 30-50nm; the modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is n-dodecyltrimethoxysilane.

[0130] The incremental filler is silicon powder.

[0131] The high temperature resistant flame retardant fiber is basalt fiber.

[0132] A method for preparing silicon dioxide ceramics comprises the following steps:

[0133] (1) preparing a silicon dioxide reinforcement material;

[0134] (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix;

[0135] (3) The dry premix is ​​added with deionized water in an amount 8 times the mass of the mixed base material, and the mixture is fed into a ball mill with a ball-to-material ratio of 1:1. The mixture is wet-milled at 300 r / min for 1 hour, filtered, dried, and crushed to obtain a ball mill material, and dried to obtain the final product.

[0136] In this comparative example, except that the silicon dioxide is not modified with sodium saccharin and ammonium polyphosphate, the other raw materials and preparation method are the same as those in Example 1.

[0137] Comparative Example 3

[0138] A silicon dioxide ceramic comprises the following raw materials in parts by weight: 40 parts of a ceramic filler, 30 parts of a silicon dioxide reinforcing material, 5 parts of a flux, 5 parts of an incremental filler, and 10 parts of high-temperature resistant flame-retardant fibers.

[0139] The ceramic-forming filler is mica powder.

[0140] The flux is low melting point glass powder.

[0141] The melting point of the low-melting-point glass powder is 400-500°C.

[0142] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0143] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20 minutes, heating in a tube furnace at 400° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0144] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is sequentially immersed in a hydrophobic modifier solution having a mass concentration of 1-2% for 3 hours. After the immersion is completed, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0145] The particle size of the nano silicon dioxide is 30-50 nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1.

[0146] The modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is n-dodecyltrimethoxysilane.

[0147] In this comparative example, except that in the hydrophobic modification of silicon dioxide, only a hydrophobic modifier solution with a concentration of 1-2% is used for immersion treatment, the other raw materials and preparation methods are the same as those in Example 1.

[0148] Comparative Example 4

[0149] In this comparative example, except that only a hydrophobic modifier solution with a concentration of 9-10% is used for immersion treatment in the hydrophobic modification of silicon dioxide, the rest of the raw materials and preparation method are the same as those in Example 1. That is:

[0150] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0151] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20 minutes, heating in a tube furnace at 400° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0152] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is sequentially immersed in a hydrophobic modifier solution having a mass concentration of 9-10% for 3 hours. After the immersion is completed, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0153] Comparative Example 5

[0154] In this comparative example, except that only a hydrophobic modifier solution with a concentration of 19-20% is used for immersion treatment in the hydrophobic modification of silicon dioxide, the rest of the raw materials and preparation method are the same as those of Example 1. That is:

[0155] The silicon dioxide reinforcing material is obtained by modifying silicon dioxide, and the specific preparation method is as follows:

[0156] (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20 minutes, heating in a tube furnace at 400° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica;

[0157] (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is sequentially immersed in a hydrophobic modifier solution having a mass concentration of 19-20% for 3 hours. After the immersion is completed, it is dried at 80-90° C. to obtain a silica reinforcement material.

[0158] Performance Testing

[0159] The products of Examples 1-5 and Comparative Examples 1-5 of the present invention were used as ceramic fillers to prepare ceramic silicone rubber, and performance tests were performed.

[0160] First, place 100 parts of silicone rubber on an open rubber mixer, add 50 parts of the filler to be tested and mix. After mixing evenly, add 1 part of D24 and continue mixing until evenly mixed. Then, place the evenly mixed rubber on a flat vulcanizer, and vulcanize it under 140°C and 10MPa to obtain the sample to be tested.

[0161] Test method:

[0162] (1) Mechanical properties: The test was conducted using a UTM4204X high and low temperature electronic universal testing machine in accordance with GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”. The tensile rate was 500 mm / min, and the test was repeated 5 times to take the average value.

[0163] (2) Oxygen index: According to GB / T 10707-2008, the limit oxygen index (LOI) of the sample was tested using an oxygen index meter. The sample was 150 mm long, (6.5 ± 0.5) mm wide, and (3 ± 0.25) mm thick. Each sample was tested 15 to 30 times, and the results were averaged.

[0164] (3) According to ASTM D2240, use a Shore hardness tester to test the Shore hardness of the sample. The thickness of the specimen shall not be less than 6 mm. Each sample shall be tested 3 times and the average value shall be taken.

[0165] (4) Ceramic conversion rate: evaluated by thermogravimetric analysis (at N 2 Under the atmosphere, the heating rate is 10 / ℃min, the gas flow rate is 60mL / min, the temperature range is 30-1000℃, the sample mass is 7-9mg), and the residual rate of the sample after reaching 1000℃ is used as the evaluation.

[0166] (5) Microstructure of ceramic body: The ceramicized silicone rubber composite material sample was heated in a muffle furnace at 800°C for 1 h to simulate the ceramicization process under fire. After the test, the cross section of the ceramic body was gold-sprayed and the microstructure of the sample was observed using a scanning electron microscope.

[0167] The experimental results are shown in Table 1:

[0168] Table 1 Performance test results

[0169]

[0170] From the data in Table 1, we can see that the ceramic silicone rubber obtained in the embodiment of the present invention exhibits good comprehensive properties, with a tensile strength of more than 10MPa, a limiting oxygen index of more than 35%, and excellent mechanical properties and flame retardant properties. However, in comparative examples 1-5, which have changed the technical means, nano-silicon dioxide is directly added, and the inorganic nanoparticles are very easy to agglomerate, and the dispersion of the filler in the substrate is reduced, resulting in a decrease in comprehensive performance. In comparative examples 3-5, which are treated with a single concentration of modifier, the degree of silane modification is weakened, and the degree of grafting is lower than that of the embodiment, resulting in weakened performance. From the electron microscope image of the cross section, we can also see that the cross section of embodiment 1 of the present invention is dense and uniform, while the comparative examples have formed a macroporous structure formed by filler agglomeration.

[0171] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A silicon dioxide ceramic, characterized in that: The raw materials include the following parts by weight: 40-60 parts of porcelain filler, 30-60 parts of silica reinforcing material, 3-5 parts of flux, 5-10 parts of bulk filler, and 10-15 parts of high temperature resistant flame retardant fiber; the silica reinforcing material is obtained by modifying silica, and the specific preparation method is as follows: (1) placing nano-silica in a container, adding sodium saccharin and ammonium polyphosphate, mixing well and grinding, grinding for 20-30 minutes, heating in a tube furnace at 400-500° C. for 2 hours, and cooling to room temperature naturally after heating to obtain preliminarily modified nano-silica; (2) Hydrophobic modification: The preliminarily modified nano-silica obtained in step (1) is soaked in hydrophobic modifier solutions with mass concentrations of 1-2%, 9-10% and 19-20% in sequence, with the soaking time being 1 hour respectively, for a total of 3 hours, and after the soaking is completed, it is dried at 80-90° C. to obtain a silica reinforcement material; The particle size of the nano silicon dioxide is 30-50nm; the mass ratio of the nano silicon dioxide, sodium saccharin and ammonium polyphosphate is 10:1:1; the modifier solution is obtained by dispersing long-chain silane in an ethanol solution, and the long-chain silane is one of n-dodecyltrimethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane or octadecyltriethoxysilane.

2. The silicon dioxide ceramic according to claim 1, characterized in that: The porcelain-forming filler is one or more of mica powder, aluminum hydroxide, clay, calcium carbonate and kaolin.

3. The silicon dioxide ceramic according to claim 1, characterized in that: The flux is one or more of low melting point glass powder, boron oxide and zinc borate.

4. The silicon dioxide ceramic according to claim 1, characterized in that: The incremental filler is silicon powder.

5. The silicon dioxide ceramic according to claim 1, characterized in that: The high temperature resistant flame retardant fiber is one of basalt fiber, glass fiber or aluminum silicate fiber.

6. A method for preparing the silicon dioxide ceramic according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: (1) preparing a silicon dioxide reinforcing material; (2) dry-mixing a porcelain-forming filler, a silica reinforcing material, a flux, an incremental filler, and a high-temperature resistant flame-retardant fiber according to parts by weight to obtain a dry premix; (3) Add deionized water in an amount of 8 to 10 times the mass of the mixed base material to the dry premix, put it into a ball mill, control the ball-to-material ratio to 1:1, wet ball mill at 300 to 500 r / min for 1 to 3 hours, filter, dry, and crush to obtain a ball mill material, and after drying, obtain the final product.

7. Use of the silicon dioxide ceramic according to any one of claims 1 to 5 as a filler in refractory silicone rubber.

Citation Information

Patent Citations

  • Lightweight low-smoke fireproof heat-insulating silicone rubber material and preparation method thereof

    CN115449225A